Objektna arhitektura na osnovi semantične zgradbe informacije - Žumer, Viljem (Informatica (Ljubljana), 1983)
The paper gives the semantic structure of information where object have scope, property, atribut and representation. Storage architecture for some interesting object is described. This concept for reliable direct execution of HLLprograms is appropriate.
Keywords: arhitektura objektov; informacije; information; krmilni stavki; object architecture; objektna arhitektura; semantic structure of information; semantična zgradba informacije